The Development of Lower Limb Exoskeleton for Stroke Patients - M. Desa, H.; I. Ideris, M.; Jailan, R.; M. Tahir, N. (International Journal of Engineering and Technology, 2018)
A new set of lower limbs exoskeleton was developed for the use of hemiplegic stroke patients. The movement of the exoskeleton according to normal gait cycle was driven by two direct currents (DC) stepper motors. These motors incorporated with the worm-gear to provide forward-reverse rotation, constant power and high torque at lower speed. It will be used to drive the hip and knee movements to support the stroke patient in restoring and regaining physical lower limb movements. Hip and knee movements exercise is important to improve blood circulation as well as to avoid the deterioration of leg muscle of the paralyzed patients. In this paper, a system was tested on 6 healthy subjects with different height and weight. The exoskeleton movement was controlled through an android application by Arduino controller. The result showed that every subject, despite having different height and weight, gave similar results in the angle but with different execution time, depending on their walking pattern.Â